ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN FREKUENSI KUNJUNGAN ANTENATAL CARE (ANC) DI PUSKESMAS LINGGA KABUPATEN KUBU RAYA KALIMANTAN BARAT TAHUN 2014 - ., Nur Annisa (ProNers, 2015)
Mother mortality is one of serious problems faced by many countries, including Indonesia. Therefore,government of Indonesia made a health program that one of its pillars is antenatal care, whichpurposed to reduce mortality and complication during pregnancy.The aim of this study is toinvestigate the correlation between knowledge level, husband"™s support, and health practitioner"™sattitude with frequency of visits for antenatal care (ANC) in Lingga Health Center, District of KubuRaya in 2014.Method: This is a quantitative study with cross-sectional approach. Sampel involved in this study is32 mothers through total sampling technique. Fisher"™s test was used for bivariate data analysis. Bivariate analysis shows that there is no significant correlation between knowledge level (p = 1.00),husband"™s support (p = 1.00), and health practitioner"™s attitude (p = 0.44) with frequency of visits forANC.There is no significant correlation between knowledge level, husband"™s support, and healthhealth practitioner"™s attitudewith frequency of visits for ANC in Lingga Health Center, Distr ict ofKubu Raya in 2014.Keywords: Antenatal care, factors, knowledge level, husband"™s support, health practitioner"™s attitude, correlation